A health and wellness transformation programme to ensure optimal student performance and well-being within ICE environments - Juanita Jonker; Ryk Lues (Journal of Student Affairs in Africa)
Introduction and aim: International research have identified numerous impacts of the COVID-19 circumstances on students, such as decreased activity, food insecurity and poor mental health. This paper proposes an intervention programme that universities could apply to prepare for similar future situations.